Foraging behaviour of stingless bee, Heterotrigona itama on star fruit trees (Averrhoa carambola L.) - Mohamad Yusoff, Siti Najwa (2017)
Pollination by an insect is important to increase fruit size at yield, hastens maturity, and produces a more symmetrical fruit shape. Malaysia is rich with native pollinator such as stingless bees, but the study about it is still lacking. Thus, the objectives of this study were: 1) To determine the frequency of foragers going out and coming back to the hive; 2) To investigate the average number of flowers visited and time taken per flower visit. The study was conducted in star fruit cultivated plot with established colonies of H. itama at Integrated Farm, Faculty of Agriculture, Universiti Putra Malaysia. Foraging bees were enumerated by using a manual tally counter to determine the number of individuals that flew out and in their hive from 0800 hours to 1300 hours. Ten foragers were selected randomly. The number of flowers visited by individuals within three minutes has been counted manually and time taken for each flower visited by an individual was measured using a stopwatch. Data obtained were subjected to one-way Analysis of Variance (ANOVA). While the number of flowers visited and time taken per flower were averaged. This study showed that there was no significant difference for the number of foragers that flew out and coming back to the hive between times. However, this study has shown that H. itama active in the morning between 0800 hours and 1030 hours while the flowers were open. The study of the average number of flower visited and time taken per flower visit showed that the overall total number of flowers visited by 30 individuals is 463 flowers. While, the most frequent number of flowers visited is 10 to 15 flowers.